Evaluation of the efficacy of celecoxib and ibuprofen on postoperative pain, swelling, and mouth opening after surgical removal of impacted third molars: a randomized, controlled clinical trial. Issue 10 (October 2019) - Isola, G.; Matarese, M.; Ramaglia, L.; Cicciù, M.; Matarese, G.
Abstract: The objective of this study was to compare the efficacy of celecoxib and ibuprofen in reducing postoperative sequelae following the surgical removal of impacted mandibular third molars. Ninety-eight subjects who needed surgical extraction of an impacted mandibular third molar were selected for the study. All subjects were randomly allocated to receive one of the following treatments twice a day for 5 days after surgery: placebo ( n = 32), ibuprofen ( n = 33), or celecoxib ( n = 33). The primary outcome chosen was postoperative pain, which was evaluated using the visual analogue scale (VAS) score recorded by each patient. The secondary outcomes chosen were changes in postoperative swelling and maximum mouth opening values compared to preoperative ones. Compared to placebo, treatment with celecoxib and ibuprofen resulted in improvements in the primary outcome. Furthermore, when compared to the other groups, patients in the celecoxib group showed a significant reduction in postoperative pain scores at 6 h ( P < 0.001), 12 h ( P = 0.011), and 24 h ( P = 0.041) after surgery. Regarding swelling and maximum mouth opening values, there were no significant differences between the groups at each follow-up session. This study demonstrated that treatment with celecoxib decreased the incidence and severity of postoperative pain following third molar surgery compared to ibuprofen and placebo.